Analysis on the Added Value of Excelsa Coffee (Coffea liberica var. dewevrei) in Wonosalam, Jombang - Sutawi; Rif'an Hariri; Noor Harini (Universitas Muhammadiyah Malang, 2023)
The district of Wonosalam in Jombang, Indonesia, harbors significant potential in the agribusiness sector, with a particular focus on Excelsa coffee. Excelsa coffee is currently being cultivated with the vision of establishing it as a signature commodity of Wonosalam. This study is dedicated to analyzing the value transformation that occurs during the conversion of coffee cherries into green beans, further processing of green beans into roasted beans, and providing recommendations for enhancing added value. The study employed a purposive sampling technique, with data analysis conducted using the Hayami method. Nineteen respondents engaged in Excelsa coffee processing participated in the study. The findings of this study demonstrate that the conversion of cherries into Excelsa coffee green beans and the subsequent transformation of green beans into roasted beans indeed contribute to increased value. Specifically, the added value of green beans for Excelsa coffee amounts to IDR 1,153 per kilogram, while the added value for red-picked Excelsa coffee reaches IDR 4,458 per kilogram. Furthermore, the added value of Random Excelsa coffee roast beans is calculated at IDR 12,525 per kilogram, with red-picked Excelsa coffee roast beans achieving an added value of IDR 35,525 per kilogram. To further enhance the added value of Excelsa coffee, improvements can be made in post-harvest quality and downstream processing of coffee.